Réponses

Meilleure réponse !
2014-04-25T23:40:54+02:00
R = 5x(2 - x) + (2x-3)(4+7x)
R = 10x - 5x² + 8x + 14x² - 12 - 21x
R = 9x² -3x - 12

S = 2(4+a)(1-3a) - (7a+2)(5-a)
S = 2(4 - 12a + a - 3a²) - (35a - 7a² + 10 - 2a)
S = 8 - 24a + 2a - 6a² - 35a + 7² - 10 + 2a
S = a² -55a  -2

T = (5y-1)² - 4y(4y-7)
T = 25y² - 10y + 1 - 16y² + 28y
T = 9y² +18y + 1
  • Utilisateur Brainly
2014-04-26T00:05:53+02:00
Exercice 8 :

R= 5x(2 - x) + (2x - 3)(4 + 7x)
  = 10x - 5x² + 8x + 14x² - 12 - 21x
  = 9x² - 3x - 12

S = 2(4 + a)(1 - 3a) - (7a + 2)(5 - a)
   = 2(4 - 12a + a - 3a²) - (35a - 7a² + 10 - 2a)
   = 8 - 24a + 2a - 6a² - 35a + 7² - 10 + 2a
   = a² - 55a  - 2

T = (5y - 1)² - 4y(4y - 7)
   = 25y² - 10y + 1 - 16y² + 28y
   = 9y² + 18y + 1

Bonne soirée à toi! :) 
merci merci merci beaucoup
Avec plaisir! :)